Dynamic response of YAG polycrystalline and single‐crystal transparent ceramics: Experiments and mesoscopic simulations. Issue 11 (15th July 2022) - Cao, Xiuxia; Li, Tong; Yu, Yin; Li, Xuhai; Qi, Jianqi; Meng, Chuanmin; He, Hongliang; Hu, Jianbo; Wu, Qiang
Abstract: Due to superior mechanical and optical properties, yttrium–aluminum–garnet (YAG) is emerging as a potential transparent armor material. Its dynamic behavior, however, remains largely unexplored. In this work, both impact experiments and mesoscopic simulations have been performed to better understand the dynamic response of YAG polycrystalline and single‐crystal transparent ceramics. Experimental results demonstrate that the two samples have remarkably different dynamic behaviors with the increasing shock pressure, in which the Hugoniot elastic limit basically keeps unchanged (∼14 GPa) in YAG polycrystalline ceramic, whereas it varies from 11 to 31 GPa in YAG single crystals. Moreover, elastic precursor decay is visible only in single‐crystal samples. Mesoscopic simulations with a lattice‐spring model reveal that the difference arises from the distinct fracture mode in the two samples. Less damage and coarser fragmentations in YAG single crystal also suggest a probability of better ballistic resistance as transparent armor materials.